2014
DOI: 10.1111/hdi.12138
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic hypotension: Frequency, sources of variation and correlation with clinical outcome

Abstract: Intradialytic hypotension (IH) is a frequent complication of hemodialysis (HD) and is associated with increased patient mortality and cardiovascular events. We studied IH to determine its variability, correlates, and clinical impact in 13 outpatient HD facilities. Blood pressure was captured by machine download. IH was defined as >30 mmHg decrease in systolic blood pressure to <90 mmHg. Risk factors were assessed by logistic regression and hospitalization by Poisson regression. Time to death and first hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
188
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(210 citation statements)
references
References 24 publications
11
188
2
9
Order By: Relevance
“…Davenport et al found that 7% of all treatments were complicated by symptomatic hypotension and that this was more common in patients with large IDWG and lower predialysis BPs and pulse pressures (15). Using a different operational definition (.30 mmHg decrease in systolic BP to ,90 mmHg), Sands et al observed that IDH occurred in 17.2% of dialysis treatments (17). And as we found, IDH in their study was strongly associated with risk of hospitalization and death compared with patients who did not experience IDH.…”
Section: Discussionmentioning
confidence: 99%
“…Davenport et al found that 7% of all treatments were complicated by symptomatic hypotension and that this was more common in patients with large IDWG and lower predialysis BPs and pulse pressures (15). Using a different operational definition (.30 mmHg decrease in systolic BP to ,90 mmHg), Sands et al observed that IDH occurred in 17.2% of dialysis treatments (17). And as we found, IDH in their study was strongly associated with risk of hospitalization and death compared with patients who did not experience IDH.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that hypotension occurs so often. Although many factors-patient or treatment related-play a role, a reduction of blood volume is crucial in its pathogenesis 1 . In our study we found 28%(26) patients developed hypotension during haemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Os pacientes com maior risco de apresentar hipotensão durante a diálise são pacientes idosos, mulheres, diabéticos, com fósforo sérico aumentado, pacientes com doença arterial coronariana, e aqueles com neuropatia autonômica. [9][10][11][12] A primeira linha de manejo da hipotensão é a cuidadosa determinação do peso seco, orientação para baixa ingesta de sódio na dieta, evitar alimentar-se durante a sessão de diálise, evitar uso de hipotensores antes da sessão, bem como o uso de temperatura mais baixa do dialisado (35° Celsius). Em segunda mão devem-se buscar métodos objetivos para determinar peso seco, como fazer uso da bioimpedância e avaliar o desempenho cardíaco com ecocardiografia e prolongar o tempo de diálise ou programar diálises frequentes.…”
Section: Síndrome Do Desequilíbrio Da Diálise (Sd)unclassified
“…Estão relacionados com esse mecanismo também fatores facilmente modificáveis como a ingestão de alimen tos, uso abundante de anti--hipertensivos, perda de sangue ao nível das conexões, temperatura do dialisado e a ruptura da membrana do dialisador, conforme a tabela 1. 1,8,9,[13][14] Os sintomas variam de tontura e sensação de desfalecimento, náuseas, calor e sudorese, dificuldades respiratórias e cãibras musculares, bocejos frequentes, dor precordial, palidez cutânea, apatia, confusão mental e taquicardia. [9][10][11][12][13] A fisiopatologia da hipotensão relacionada com a ultrafiltração (UF) excessiva é compreendida da seguinte Páginas 03 de 05 não para fins de citação surge ou muda de padrão a partir do início do tratamento dialítico, de característica pulsátil, em topografia bifrontal, cuja intensidade varia de intensidade de moderada a forte no decorrer do procedimento.…”
unclassified
See 1 more Smart Citation